SISTEM INFORMASI TATA NASKAH DINAS ELEKTRONIK DI INSTANSI KECAMATAN PANDAAN DAN PEMERINTAH DESA MENGGUNAKAN METODE WATERFALL - Kurniawan Wahyu Haryanto; Muhammad Bakhruddin (SPIRIT, 2021)
Abstract : Official script management is written information as an official communication tool made by authorized officials in government agencies. In terms of making official manuscripts in Pandaan District, they still use manual processes so that the service process is slow. The existence of these problems the writer will implement good governance by creating an electronic service manuscript information system using the waterfall method implementation, with the hope of producing an organized system. The results of this research are in the form of an electronic official script management information system using the waterfall method with the hope of facilitating the work of the State Apparatus.